Psychometric validation of an Arabic version of the WHO-5 wellbeing index among Lebanese adolescents - Rita Doumit; Souheil Hallit; Maria-Jose Sanchez-Ruiz; Myriam El Khoury-Malhame (PLoS ONE, 2025)
Introduction Wellbeing in adolescence is frequently associated with positive developmental outcomes. The WHO-5 is widely recognized for its brevity, clarity, robust reliability, and cultural validity. In this study, we aimed to assess the psychometric properties of an Arabic version of the WHO-5 scale among Lebanese adolescents. Methods This cross-sectional study involved 700 Lebanese school students aged 14−19 years. Participants were assessed using WHO-5 wellbeing index (WHO-5) (wellbeing), PHQ-9 (depression), and GAD-7 (anxiety) Arabic questionnaires at two-time points, 3 months apart. Results We found that the 5 items of the WHO-5 converged into a single factor. Internal consistency of scores was adequate in the total sample (ω = .83/ α = .83). The convergent validity for this model was satisfactory. We were able to show the invariance across gender at the configural, metric, and scalar levels, with males showing a higher level of wellbeing compared to females. The pre-posttest assessment for the WHO-5 scale was conducted on 358 participants; the intraclass correlation coefficient was adequate = 0.78 [95% CI .73; .82]. Our analyses also show that wellbeing was negatively correlated with depression (r = −.54; p < .001) and anxiety (r = −.52; p < .001). Conclusion The Arabic WHO-5 among Lebanese adolescents displayed highly satisfactory psychometric properties, which are evidence of its validity. It could be used to better track positive mental health in this vulnerable age group and could highlight efficiency in interventions aiming to promote wellbeing in adolescents. It could also potentially identify at risk individuals.